Challenges of measuring media audiences in the digital environment - Chaoua, Hiba (Journal of Ecohumanism, 2026)
Audience measurement studies are not limited to simply collecting and analyzing data; they extend to building strategic insights that contribute to developing media content, guiding marketing decisions, and enhancing audience engagement.The study concluded that one of the requirements of audience studies in the digital media age is the necessity of combining inquiries about user interaction with on-screen content with a description of the context of that interaction, including motivations, locations, timelines, and a map of the digital media network used, etc. This is despite the fact that it requires time-consuming projects, often employs multiple methodologies, and demands advanced technical skills.